9. PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI HUMAN TRAFFICKING DI UKRAINA PADA TAHUN 2010-2014 - I.G, Sukmastuti Putri; Utomo, Tri Cahyo; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Ukraine is a former Soviet country located in the Eastern Europe with strategicgeographical and geopolitical advantage as the country directly borders Asia and Europe.During 1990, due to poverty and law employment, many Ukrainian women migrated andthus created a market for human trafficking. Ukraine is placed the 2nd tier watch by the USbecause the Ukrainian government does not follow the minimum standard for reducinghuman trafficking although significant effort has been made to adhere to the minimumstandard stated. IOM is an NGO that has become Ukrainian’s biggest partner in combatinghuman trafficking. Since 2000, the IOM office in Ukraine has been the center to give helpto the victims of human trafficking. This research aim to take a closer look at the humantrafficking cases in Ukraine. Case studies and interviews have been a method used tounderstand the role of IOM in overcoming such cases from 2010 to 2014. The study foundthat IOM has played a big part I helping Ukrainian government combatting humantrafficking, in that organization has helped reducing victims and increasing regulation from2010 to 2014.